2023
DOI: 10.1093/asjof/ojad053
|View full text |Cite
|
Sign up to set email alerts
|

The Health Impacts, Prevalence, and Acceptance Level of Cosmetics Interventions Among Females in Saudi Arabia

Abstract: Background With the rising global desire for beauty, cosmetic interventions have increased. Saudi Arabia ranked 29th among the top 30 fastest-growing countries for cosmetic procedures. Objectives This study aims to investigate the prevalence, acceptance level, and health impacts of cosmetic interventions among females in Saudi Arabia. Methods This cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
1
1
Order By: Relevance
“…Meanwhile, knowing the adverse events of cosmetic interventions was associated with a low level of acceptance with a P value less than 0.001. 14 The prevalence of cosmetic surgery in our study was slightly higher (13.9%) compared with that in the previous study. Most of our participants (70.5%) were aware of the complications of cosmetic surgery.…”
contrasting
confidence: 75%
See 1 more Smart Citation
“…Meanwhile, knowing the adverse events of cosmetic interventions was associated with a low level of acceptance with a P value less than 0.001. 14 The prevalence of cosmetic surgery in our study was slightly higher (13.9%) compared with that in the previous study. Most of our participants (70.5%) were aware of the complications of cosmetic surgery.…”
contrasting
confidence: 75%
“…The major reasons for cosmetic surgery among Saudi women, as reported in a previous study, included medical reasons (46.8%), followed by beauty (26.3%), whereas the remaining factors were less common and included increased self-esteem (12.9%) and reconstructive reasons (11.1%). 14 In the current study, the major derivative for increasing the probability of undergoing cosmetic surgery was dissatisfaction with appearance, followed by social media; the medical reasons were not assessed. This variation in findings between this study and the previous study may be due to the variation of the investigated factors.…”
mentioning
confidence: 83%
“…In a recent cross-sectional study conducted among Saudi females, 10% of the participants were found to have undergone cosmetic procedures, including operative and non-operative procedures. 10 In another study conducted in 2012 in Jeddah, Saudi Arabia, only 2.2% of female college students surveyed had undergone cosmetic surgery. 11 This overall increase in the prevalence of cosmetic surgery among college students is reflected in the literature.…”
Section: Discussionmentioning
confidence: 97%
“…In presnt study 1% of emergency department nurses had suffered physical attack at work.In contrast to present study, research studies from Turkey, Iran, Saudi Arabia, Taiwan, and Jordan showed 19.7%, 19.7%, 30%, 45%, and 63.9% physical abuse rates, respectively [19][20][21][22][23] . A study done in Saudi Arabia found 14 cases of doctors and nurses were reported to be attacked with weapons and devices 24 . A lack of security officers in public hospitals, a lack of preventative measures, and more disorganized admissions processes may explain why they get hit by healthcare-associated infections more often 25 .…”
Section: Discussionmentioning
confidence: 99%